Rape Crisis Counseling: Trauma Contagion and Supervision - Rizkalla, Niveen (Journal of interpersonal violence, 2021)
This study of rape crisis counselors considers whether increased exposure to victims’ trauma is associated with increased supervision—believed necessary to combat trauma contagion—and whether such supervision will reduce the negative impact of such exposure. One hundred six women counselors in seven of nine rape crisis centers in Israel completed anonymous questionnaires documenting their work and trauma exposure. Trauma exposure was defined by counselors’ number of victim-contact hours per week and their assessment of the trauma severity they experienced. Supervision was measured by the number of hours received. Counselors trauma outcome indicators included sexual intimacy, secondary traumatization (evidenced in posttraumatic stress disorder [PTSD]-type symptomology), and vicarious traumatization (expressed as a disturbance in cognitive schemes that undermine the self and others). Hypotheses were evaluated in fully recursive path analyses via ordinary least squares (OLS) regression. Participants’ mean age was 43.4 years; 58% were married, 26% single, 13% divorced, and 3% widowed; 81% had a college degree or more; 18.9% reported being exposed to victims-trauma at a minimal level, 54.7% moderate and 26.4% extreme; and 43.4% were abused at some time in their lives. Job exposure to victims’ trauma was significantly associated with increases in supervision time (β = .33, p = .002). Supervision time fully mediated the relationship between duration of exposure to victims’ trauma and counselors’ secondary traumatization reports such that increased supervision was associated with degrading sexual intimacy (β = .22; p = .032) and increased Secondary Trauma Scale scores (β = .44; p = .004) after taking into account counselors’ education level, history of abuse, anger management in intimate relationship, and posttraumatic growth scores. The study results raise concern about counselors’ mental health in that the supervision effect exacerbated the trauma contagion impacts. The study suggests a need for documenting the nature of the supervision and considering different types of supervision methods.